Vegetable and Fruit Production - Abbey, Lord; Ampofo, Josephine; MacDonald, Mason (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
To ensure global food and nutrition security, there is a need for a sustainable year-round supply of nutritious food systems such as fruits and vegetables. Over the years, there has been a surge in fruit and vegetable consumption due to their composition of health-promoting biomarkers such as vitamins, minerals, fiber, and bioactive polyphenols. However, producing fruits and vegetables with the valuable contents of these health-promoting biomarkers is dependent on various factors, such as growing degree days, genetic pool, and management practices. Thereby, the goal of this Special Issue (Fruits and Vegetables Production) of the MDPI journal Plants was to provide up-to-date knowledge on traditional and emerging novel technologies applicable in sustainable production of high-value fruits and vegetables at various stages of their field and greenhouse production chains. In summary, this reprint is produced from the Special Issue that reported 12 peer-reviewed manuscripts, with foci on: (1) crop response to different elicitors and (2) green non-destructive technologies for efficient profiling of biomarkers, quality parameters, and cultivar evaluation. Thus, this reprint bridges the gaps among stakeholders (i.e., researchers, policymakers, and industry) for efficient production of consumer-centric crops with high productivity, appreciable nutritional value, and post-harvest resilience.